Prevalence of undiagnosed depression among patients with hypertension: a cross-sectional study of Malaysian primary care perspective - Choong, Siaw Mei; Lee, Ping Yein; Abdul Rashid, Aneesa (Academy of Family Physicians of Malaysia, 2023)
Introduction: This study aimed to determine the prevalence of suspected depression and its associated factors among patients with hypertension in a Malaysian primary care clinic. Methods: This cross-sectional study was conducted in a primary care clinic from 1 June to 31 August 2019 using the Patient Health Questionnaire-9. Results: The prevalence of suspected depression was 9.0%. The significant predictors of depression were Indian ethnicity (adjusted odd ratio [AOR]: 2.373; confidence interval [CI]: 1.147–4.907), divorce (AOR: 3.5; CI: 1.243–9.860), singleness (AOR: 2.241; CI: 1.182–4.251), heavy episodic drinking (AOR: 7.343; CI: 2.494–21.624), low physical activity level (AOR: 1.921; CI: 1.093– 2.274), low fibre intake (AOR: 1.836; CI: 1.061–3.178), uncontrolled blood pressure (AOR: 1.800; CI: 1.134–2.858) and presence of hypertension complications (AOR: 3.263; CI: 2.053–5.185). Conclusion: Primary health care providers must screen for depression among patients with hypertension, particularly those within high-risk groups, and implement interventions that address modifiable risk factors.